Cracking the Wealth Puzzle: Investigating the Interplay of Personal Finance, Expenditure Behavior, and Financial Management - Lulaj, Enkeleda (Ekonomika, 2024)
This paper investigated the wealth puzzle by examining the relationships among personal finance (PF), expenditure behavior (EB), and financial management (FM). Data from a diverse sample of 2000 individuals across regions such as Kosovo, Ghana, Kenya, Nigeria, Turkey, Pakistan, Nepal, Uganda, Cameroon, Ethiopia, India, Indonesia, Albania, Oman, and Egypt were collected through an online questionnaire from 2023 to 2024, and processed through exploratory and confirmatory factor analyses using AMOS and SPSS programs. Results revealed the robust relationships among PF, EB, and FM, indicating their resilience and strong internal consistency, and underscoring their pivotal role in shaping individuals’ financial stability and well-being. Notably, EB emerged as a crucial determinant, highlighting the importance of aligning spending habits with family priorities, moderating excesses, and consistently reviewing for improvements. Moreover, critical variables within PF and FM underscored the necessity for strategic financial planning, efficient spending optimization, and the cultivation of resilience against unforeseen financial obstacles. This research has significantly advanced the understanding of wealth dynamics and provided practical insights for policymakers and educators to design targeted financial education initiatives that can improve financial well-being and long-term prosperity. Future research should concentrate on understanding underlying mechanisms and assessing intervention effectiveness across more variables and countries.